Uniform Step Loading of a Partial Interaction Composite Beam - Al-Joani, Shaimaa; Kurdi, Nahidh (Iraqi Journal of Civil Engineering, 2022)
In the present paper, a one-dimensional finite element model for the analysis of composite beams of partial interaction is constructed. This model was verified against some analytical results available in the literature and achieved very good agreement with the natural frequencies and the time histories it was compared to. Then it was utilised to analyse partial interaction composite beams under the effect of uniform step loads and provided important information about the expected dynamic amplification factors, which turned out to be particularly high, and the effects of the linear stiffness ratio of the interface and the boundary conditions of the lower layer of the beam. The results, in particular, showed that even for extreme cases the orders of magnitude of the slip and the corresponding uplift remain the same. This pointed out an important finding that the uplift in the researched context, at least, is not negligible as it is widely assumed in the literature.